Information and technology law implementation on enforcing criminal sanctions for online gambling - Aziza, Dimas Arya (Indonesian Journal of Multidisciplinary Science, 2023)
Gambling is one of the most important problems considered by all levels of Indonesian society. The emergence of the Internet of Things (ITE) Law in Indonesia has resulted in the development of a new crime that is rife, namely gambling carried out online. This article discusses several formulations of problems including law enforcement for online gambling crimes based on the ITE Law and how criminal sanctions can be imposed on online gambling criminals. The article explains the enactment of the principle of lex specialis derogat legi generalis which applies more specific rules than general rules.